CHROMATOGRAPHIC EVALUATION OF DIFFERENT EXTRACTS OF VENTILAGO MADERASPATANA GRAETN. - Ahire, Sujeetkumar I.; Ahire, Sandhya S.; Jain, Akshata A. (Journal of Global Pharma Technology, 2024)
Chromatographic studies were carried out on leaves and stem extracts of Ventilago maderspatana Gaertn belonging to the family Rhamnaceae. It is an important and well known plant in the Indian system of medicine. Leaf and stem samples of V. maderspatana were subjected to maceration by using distilled water and ethanol. Aqueous and ethanolic extract were prepared from the leaf, stem of Ventilago maderspatana. Preliminary phytochemical analysis was carried out for all extracts. All extract were found to contain different phytoconstituents such as alkaloids, glycosides, steriods and sterols, saponins, flavonoids, carbohydrates, and tri- terpenoids and showed the absence of amino acids, proteins and acidic compounds. Extract were subjected to TLC and HPTLC analysis. Keywords: V. maderspatana, Leaf and Stem extract, Chromatographic evaluation.